Memahami Keterampilan Dan Nilai Sebagai Materi Pendidikan Dalam Perspektif Islam - Nauval Ardian Saputra; Rasydan Muhammad Nafis; Rere Rejo Sasmito; M. Yunus Abu Bakar (JOURNAL SAINS STUDENT RESEARCH, 2024)
This article deals with educational material, especially skills and values, as well as their importance in the context of Islamic education. Educational material is described as a key element in the educational process that includes knowledge, skills, and value. Discussions about skills include the definition, type, and urgency, where skills are considered as the technical ability to perform an action. Meanwhile, value is described as the quality or quality of something, which plays an important role as a guideline of human behavior. This article also highlights the factors that influence skills and various kinds of values. In addition, this article emphasizes the importance of value education in shaping individuals who are moral and able to manage lives in accordance with the noble values of humanity